Similar Anti-Inflammatory Acute Responses from Moderate-Intensity Continuous and High-Intensity Intermittent Exercise - Cabral-Santos, Carolina (J Sports Sci Med, 2015)
The purpose of this study was to compare the effect of high-intensity intermittent exercise (HIIE) versus volume matched steady state exercise (SSE) on inflammatory and metabolic responses. Eight physically active male subjects completed two experimental sessions, a 5-km run on a treadmill either continuously (70% vVO(2)max) or intermittently (1:1 min at vVO(2)max). Blood samples were collected at rest, immediately, 30 and 60 minutes after the exercise session. Blood was analyzed for glucose, non-ester fatty acid (NEFA), uric acid, lactate, cortisol, and cytokines (IL-6, IL-10 and TNF-α) levels. The lactate levels exhibited higher values immediately post-exercise than at rest (HIIE 1.34 ± 0.24 to 7.11 ± 2.85, and SSE 1.35 ± 0.14 to 4.06±1.60 mmol·L(-1), p < 0.05), but HIIE promoted higher values than SSE (p < 0.05); the NEFA levels were higher immediately post-exercise than at rest only in the SSE condition (0.71 ± 0.04 to 0.82±0.09 mEq/L, respectively, p < 0.05), yet, SSE promoted higher values than HIIE immediately after exercise (HIIE 0.72±0.03 vs SSE 0.82±0.09 mEq·L(-1), p < 0.05). Glucose and uric acid levels did not show changes under the different conditions (p > 0.05). Cortisol, IL-6, IL-10 and TNF-α levels showed time-dependent changes under the different conditions (p < 0.05), however, the area under the curve of TNF-α in the SSE were higher than HIIE (p < 0.05), and the area under the curve of IL-6 in the HIIE showed higher values than SSE (p < 0.05). In addition, both exercise conditions promote increased IL-10 levels and IL-10/TNF-α ratio (p < 0.05). In conclusion, our results demonstrated that both exercise protocols, when volume is matched, promote similar inflammatory responses, leading to an anti-inflammatory status; however, the metabolic responses are different.